1979
DOI: 10.2307/1936959
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Dynamics and a Phosphorus Budget of an Alluvial Cypress Swamp in Southern Illinois

Abstract: Annual patterns in hydrology, phosphorus circulation, and sediment dynamics were studied in a southern Illinois, USA floodplain swamp dominated by bald cypress (Taxodium distichum) and swamp tupelo (Nyssa aquatica). The study emphasized the swamp's interactions with the adjacent river. For the year, major inputs of water to the swamp were throughfall (74.3 em) and runoff (69.4 em) with minor contributions due to groundwater (21.6 em). Outflows were by evapotranspiration (72.3 em), surface outflow (56.5 em), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(115 citation statements)
references
References 23 publications
1
112
1
1
Order By: Relevance
“…Hydrologic conditions are extremely important for the maintenance of a floodplain wetland's structure and function, because they affect many abiotic factors, including soil anaerobiosis, nutrient availability (Mitsch and Gosselink, 2007;Vorosmarty and Sahagian, 2000). The hydrology of a river wetland creates unique physiochemical conditions that make such an ecosystem different from both well-drained floodplain systems and deeper old river bed systems.…”
Section: Wetland Hydrologymentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrologic conditions are extremely important for the maintenance of a floodplain wetland's structure and function, because they affect many abiotic factors, including soil anaerobiosis, nutrient availability (Mitsch and Gosselink, 2007;Vorosmarty and Sahagian, 2000). The hydrology of a river wetland creates unique physiochemical conditions that make such an ecosystem different from both well-drained floodplain systems and deeper old river bed systems.…”
Section: Wetland Hydrologymentioning
confidence: 99%
“…Water depth, flow patterns, and duration and frequency of flooding, sediments and nutrients transport (Kadlec and Knight, 1996;Magnuszewski et al, 2007;Altinakar et al, 2006;Kiedrzyńska et al, 2008a;Kiedrzyńska et al, 2008b), which result from all hydrologic inputs and outputs, influence the biochemistry of the soils and are major factors in the ultimate selection of the biota of wetlands (Mitsch and Gosselink, 2007;Kiedrzyńska et al, 2008a). The water status of a wetland defines its extent and determines the species composition in a natural floodplain wetland (Mitsch and Gosselink, 1993).…”
Section: Wetland Hydrologymentioning
confidence: 99%
See 2 more Smart Citations
“…11.6). However, it should be noted that the input of nutrients adsorbed to sediment was not included in the flooding assessment, which could be a very important input source of P in fens (Mitsch et al 1979). The dominant role of soil processes in setting nutrient availabilities along the productivity gradients demonstrated that human alterations of site conditions, such as drainage, have been a major cause of nutrient enrichment for N, P, and K (Olde Venterink et al 2002).…”
Section: Change In Nutrient Budgetsmentioning
confidence: 99%